Wspólnoty religijne a digitalizacja na przykładzie Kościoła katolickiego w Polsce (Przegląd Religioznawczy – The Religious Studies Review, 2025)
Nowadays digital technologies are tools, which enable the Churches and religious communities to widely propagate religious content. At the same time, tendencies under the banner of secularization are becoming more and more noticeable, which is visible not only in Western European countries, but also in Poland.New technologies have acquired particular significance for religious entities during the time of the COVID-19 pandemic due to the need for maintaining contact and bond with the congregation. The end of the pandemic has made it possible to return to traditional forms of activity. However, for many religious communities the space created in the digital sphere has remained a crucial element of their activity. To what extent can the actions taken by the religious communities, especially by the Catholic Church, suppress the secularization tendencies in Poland? To what degree is religion in the digital form attractive to the contemporary believer in Poland? An attempt to answer these boundary questions will be made on the basis of the results of the research conducted within the international project RECOVIRA.